BMP Gene‐Immobilization to Dental Implants Enhances Bone Regeneration. Issue 22 (25th June 2022) - Maekawa, Shogo; Cho, Young‐Dan; Kauffmann, Frederic; Yao, Yao; Sugai, James V.; Zhong, Xiaoyang; Schmiedeler, Caroline; Kinra, Nitin; Moy, Alyssa; Larsson, Lena; Lahann, Joerg; Giannobile, William V.
Abstract: For individuals who have experienced tooth loss, dental implants are an important treatment option for oral reconstruction. For these patients, alveolar bone augmentation and acceleration of osseointegration optimize implant stability. Traditional oral surgery often requires invasive procedures, which can result in prolonged treatment time and associated morbidity. It has been previously shown that chemical vapor deposition (CVD) polymerization of functionalized [2.2]paracyclophanes can be used to anchor gene encoding vectors onto biomaterial surfaces and local delivery of a bone morphogenetic protein (BMP)‐encoding vector can increase alveolar bone volume and density in vivo. This study is the first to combine the use of CVD technology and BMP gene delivery on titanium for the promotion of bone regeneration and bone to implant contact in vivo. BMP‐7 tethered to titanium surface enhances osteoblast cell differentiation and alkaline phosphatase activity in vitro and increases alveolar bone regeneration and % bone to implant contact similar to using high doses of exogenously applied BMP‐7 in vivo. The use of this innovative gene delivery strategy on implant surfaces offers an alternative treatment option for targeted alveolar bone reconstruction. Abstract : This innovative study is the first to combine the use of chemical vapor deposition (CVD) technology and bone morphogenetic protein (BMP) gene delivery on titanium implant surfaces as an alternative treatment option for targeted alveolar bone reconstruction and the promotion of bone regeneration in vivo.